The Aggelia in Pindar - Nash, Laura L. (Garland, 1990)
Thesis (Ph. D.)–Harvard University, 1976.
Zugl.: Harvard Univ., Diss., 1976
Keywords: Hochschulschrift; Pindar <522 or 518-438 B.C>; Pindare <0518-0438 av. J.-C.> - Critique et interprétation; Pindar; Pindarus; Epinicia; Athletics in literature; Conquerors in literature; Games in literature; Laudatory poetry; Greek; Messengers in literature; Success in literature; Sieger; Sieg; Proklamation; Verkündigung